Revision of Angursa (Arthrotardigrada: Styraconyxidae) with the description of a new species from Japan - Fujimoto, Shinta; Hansen, Jesper Guldberg (European Journal of Taxonomy, 2019)
We re-examined the type material of five of the seven described species of the marine tardigrade genus Angursa Pollock, 1979, namely, A. abyssalis Renaud-Mornant, 1981, A. bicuspis Pollock, 1979 (type species), A. capsula Bussau, 1992, A. lanceolata Renaud-Mornant, 1981, and A. lingua Bussau, 1992. In addition, we describe A. seisuimaruae sp. nov. from the Sea of Kumano, Japan. Based on new data obtained, we amend the diagnosis of this genus, provide a taxonomic key to species, and discuss their geographical distributions.